Digit ratio and hair color relationships with coronary atherosclerotic markers. (June 2019) - Nafakhi, Hussein; Al-Mosawi, Abdulameer A; Mudhafar, Mundher M; Al-Nafakh, Hasan A; Alsaady, Rana
Objective: We aimed to investigate the association between body phenotype markers and coronary atherosclerosis markers. Methods: Eighty-nine patients (mean age 57 ± 9 years, 50.5% male) who were assessed for coronary artery disease by 64-slice multidetector computed tomography angiography were enrolled in the study. Results: A significant positive association was observed between coronary artery calcification and the second to fourth digit ratio ( r  = 0.2, p  = 0.00); more notably in males compared to females ( p  = 0.03 vs. p  = 0.08). There was a significant association between coronary artery calcification and pure white hair ( p  = 0.00). There was no significant association between pericardial fat volume and second to fourth digit ratio ( p  = 0.8). Pericardial fat volume was significantly associated with pure white hair ( p  = 0.02). A significant association was observed between coronary plaque and a higher second to fourth digit ratio ( p  = 0.01) and this was more notable in males ( p  = 0.04). A significant association was observed between pure white hair and coronary plaque ( p  = 0.00). After adjustment for conventional cardiac risk factors, the association of coronary artery calcification and coronary plaque with the second to fourth digit ratio did not persist, whereas the association of pericardial fat volume and coronary artery calcification with pure white hair remained significant ( p  = 0.01 and p  = 0.00, respectively). Conclusion: These results suggest a possible predictive value of hair color, rather than digit ratio, in assessing increased risk of coronary atherosclerosis and cardiac fat deposition.